Prospective Teachers’ Commognitive: The Pedagogical Knowledge in Designing Mathematics Class for Proving Trigonometric Identity - Zayyadi, Moh.; Lanya, Harfin; Linarsih, Yanti; Nusantara, Toto; Septiadi, Dimas Danar; Ningtyas, Yoga Dwi Windy Kusuma (Jurnal Pendidikan MIPA, 2024)
This research aims to describe the pedagogical commognitive framework of prospective teachers in designing and teaching mathematics class for trigonometric identity sub materials. This type of research is qualitative research with a descriptive approach. Determination of the subject in this study using a purposive sampling technique. The subjects of this study were prospective teacher students who were undergoing microteaching learning. The pedagogical skills would be observed from their design and teaching practices activities which consist of the introduction activities, main activities, and closing activities. Researchers tried to combine commognitive and pedagogical knowledge to analyze the data. There are four components of commognitive were used in pedagogical knowledge. Those are word use, visual mediator, routine, and narratives. The main instrument in this study is the researcher himself because the researcher himself is planning, implementing, collecting data during the research through recording video and audio learning, observing, or interviewing the subject and reporting the results of the study. Word use is used as a keyword and the initial information given to students in accordance with the material to be taught. The use of the word use component is done by means of spoken orally. Visual mediators used in learning activities are prospective teacher students using laptop and blackboard media in explaining learning material, giving examples of questions, and several other learning activities. The method that prospective teacher students use in presenting material using sample questions, reminding the previous material, in providing understanding to new students then forming a conclusion (inductive approach). In addition, prospective teacher students provide understanding and focus on the concepts of the material being taught then provide questions, questions, and exercises in supporting student understanding (deductive approach).         Keywords: pedagogical commognitive, designing mathematics, prospective teachers, trigonometric identity.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp946-960